2014
DOI: 10.1177/0194599814560140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of n‐Butyl‐2‐cyanoacrylate on the Tensile Strength and Pressure Resistance of Tracheal Anastomoses Ex Vivo

Abstract: n-Butyl-2-cyanoacrylate had no significant effect on tensile strength. However, its application on the suture line provided extra pressure resistance ex vivo. We believe that further studies need to be conducted to investigate its long-term effects and histological impact on tracheal anastomoses in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…4,5,15) Bicer et al, in sheep, they found the rupture tension as 171.9 Newtons. 16) In this study, the GM of our cases was 17032.2 grams-force (167.03 Newtons), 14594.8 grams-force (143.13 Newtons), and 12852.1 grams-force (126.04 Newtons) for Groups 1, 2, and 3, respectively. From this perspective, our study data are consistent with the literature.…”
Section: Discussionmentioning
confidence: 44%
“…4,5,15) Bicer et al, in sheep, they found the rupture tension as 171.9 Newtons. 16) In this study, the GM of our cases was 17032.2 grams-force (167.03 Newtons), 14594.8 grams-force (143.13 Newtons), and 12852.1 grams-force (126.04 Newtons) for Groups 1, 2, and 3, respectively. From this perspective, our study data are consistent with the literature.…”
Section: Discussionmentioning
confidence: 44%
“…Many studies have described the use of NBCA as a tissue adhesive. NBCA has been used with variable success rates for the treatment of bone fractures, ossicular fixation, embolization, fistulas, and hemostasis of esophageal varices or bleeding gastric ulcers as well as for vascular or tracheal anastomoses [71316171819202122232425]. These remarkable studies attempted to show the potential applications of NBCA.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous ex-vivo study, it was reported that the application of n-butyl-2-cyanoacrylate to the site of the anastomosis in the trachea had beneficial effects in terms of intraluminal pressure. However, another study on rats revealed this application's inflammatory effects, which may undermine its usage in vivo [5,22].…”
Section: Discussionmentioning
confidence: 99%
“…Groups 1 and 3 were subjected to tensile strength experiments and Groups 2 and 4 were subjected to pressure experiments. The tensile strength experiment was performed by using an electronic spring scale, with the force needed to break anastomosis being recorded [5] (Figure 2). For the pressure experiment, a sphygmomanometer was attached to a cuffed 8.5 mm endotracheal tube, with the pressure at air leakage observed being recorded [5] ( Figure 3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation